Prevalence of Helicobacter pylori infection in adult patients with dyspeptic symptoms in Abdi Waluyo Hospital Jakarta from January 2017 to December 2019 - Maureen Irawati; Felix Aloysius Budimutiar; Guntur Darmawan; Deborah Theresia Budimutiar; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2021)
Background: Helicobacter pylori infection is a global public health problem and may be present in more than half of the world’s population Prevalence in developing country higher compared to developed country. However, in Indonesia prevalence of Helicobacter pylori infection is still low compare to other Asian countries. This study aims to determine the prevalence of Helicobacter pylori infection in Abdi Waluyo Hospital Jakarta from January 2017 to December 2019.Method: In this cross sectional study, a total of 772 adult patients were tested using Urea Breath Test-14C for detection of isotopic carbon produced by Helicobacter pylori ability to broke down urea.Results: Prevalence of Helicobacter pylori infection in Abdi Waluyo hospital between January 2017 – December 2019 was 20.98% with endoscopic findings as follows: 17.48% with gastritis, 3.24% with gastric ulcers , 0.26% with gastric cancerConclusion: Increase prevalence of Helicobacter pylori infection every year in Abdi Waluyo hospital. It is suggested to perfom Urea Breath Test for adult patients with dyspeptic symptoms to screened Helicobacter pylori infection.